I can bead - Annie's (Berne Annie's, 2012)
The basic techniques of jewelry making are learned through these 11 entertaining and stylish projects for preteen crafters. Beginning with a simple stretch bracelet and progressing into stringing, chains, crimps, closures, and simple loops, each project teaches a new technique and reinforces previous lessons. Simple step-by-step instructions are enhanced with drawings and photos that will help young beaders complete each project successfully and foster creative confidence. The bright and trendy jewelry is designed specifically for beginners and can be completed in just a few hours, making this
General instructions -- Lesson 1. Sherbet ice stretch bracelet -- Lesson 2. Floral stretch ring -- Lesson 3. Illusions of summer -- Lesson 4. Rock star -- Lesson 5. Interchangeable charms -- Lesson 6. Rockin' dangle -- Lesson 7. Friendship braid -- Lesson 8. Glam queen -- Lesson 9. Flower power earrings -- Lesson 10. Glitter glam -- Lesson 11. Cherry blast
2
Keywords: Beadwork; CRAFTS & HOBBIES -- Jewelry; Costume jewelry; JUVENILE NONFICTION -- Crafts & Hobbies; Jewelry making